Answer:
6
Step-by-step explanation:
3+x+x=15
3+2x=15
2x=15-3
2x=12
x=12/2
x=6
Answer:
=1.23*10^6
Step-by-step explanation:
We have to calculate
(1.93*10^7 )-(9.7*10^6)
In order to add or subtract two numbers in scientific notation, we have to make sure that the power of exponents in both numbers is same.
We have to reduce the power of 10 in first number from 7 to 6
So,
Step 1:
1.93*10^7=1.93*10*10^6
=10.93*10^6
Now,
Step 2:
=(1.93*10^7 )-(9.7*10^6 )
= 10.93*10^6- 9.7*10^6
Step 3:
=(10.93-9.7)*10^6
=1.23*10^6
Answer:
0.08
Step-by-step explanation:
As the time go the grass height go through increasing and decreasing